Effects of infliximab on lung and circulating natural killer cells, CD56+ T cells and B cells in sarcoidosis - Kullberg, Susanna (BMJ Open Respir Res, 2021)
BACKGROUND: Tumour necrosis factor α (TNF-α) is pivotal in sarcoid granuloma formation, and inhibitors of TNF-α offer an attractive third-line treatment option in sarcoidosis. The sarcoid inflammation is characterised by an exaggerated T helper 1 response, and evidence indicates a contribution of dysregulated and/or deficient NK (natural killer) cells, CD56+ T cells and B cells. OBJECTIVES: Insight into how TNF-α inhibitors influence these cells may provide more information on inflammatory mechanisms in sarcoidosis and improve understanding of such treatment. We therefore evaluated treatment effects of the TNF-α inhibitor infliximab on lung and peripheral blood (PB) NK, CD56+ T cells and B cells. METHODS: Fifteen patients were assessed with PB samples, spirometry and CT scan, and 11 of them also underwent bronchoalveolar lavage (BAL) close to start of infliximab treatment. These investigations were repeated after 6 months of treatment. RESULTS: Twelve out of 15 patients disclosed a clinical improvement at follow-up. Median percentage of BAL fluid (BALF) CD56+ T cells increased while a decrease was seen in PB (p<0.05 and 0.005, respectively). No significant changes were observed for NK cells. There was a trend towards increased median percentage of PB B cells (p=0.07), and a negative correlation was observed between PB and BALF B cells after treatment (p<0.05). CONCLUSION: In conclusion, 6 months of infliximab treatment in patients with sarcoidosis, of whom the majority benefited from the treatment, influenced immune cells in the lung and circulation differently, highlighting the importance of investigating several compartments concomitantly when evaluating treatment effects on the inflammatory activity.